Observing the Unobservable: Migrant Selectivity and Agentic Individuality Among Higher Education Students in China and Europe - Nuhoḡlu Soysal, Yasemin; Cebolla-Boado, Héctor (Frontiers in Sociology, 2020)
The research in migrant selectivity largely overlooks the broader institutional processes that shape the extent to which migrants from different backgrounds are indeed positively selected. This is particularly true in the case of highly skilled migrants, whose selection may not be conditioned by migration but by education. This paper deals with this limitation by studying individual characteristics, which are often treated as unobserved selectivity, among a specific flow of educational migrants in Europe, namely Chinese higher education students. To do so we use a unique representative multi-country dataset of about eight thousand Chinese international students and their native-born counterparts in China, the UK, and Germany. Our evidence rules out positive selection of migrants on individuality traits such as ambition, creativity, or being a risk-taker or independently minded. This supports our argument that the prevalence of agentic models of individuality is embedded in tertiary education on a global level.